2016
DOI: 10.21837/pmjournal.v14.i4.169
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Overview of Road Hump Effects on Traffic Speed in Residential Environments

Abstract: This paper is part of an ongoing study to analyse the effectiveness of road humps as a traffic calming measure in improving the residential living environment. A review was conducted on various literatures concerning the effects of road humps on vehicle speeds, particularly in residential areas. The major findings from the literatures are that the vehicles’ operating speeds are affected by the hump design and spacing in between humps. An incorrect hump profile will also potentially result in passenger discomfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…On the other hand, the analogous measure consisting of the sequence of speed tables in Zone 2 (h = 4 cm) results in a significant tendency of road users to drive at speeds above the 30 km/h limit, which is insufficient overall to fulfil the task of limiting speed within the prescribed limit. These results are in agreement with numerous previous studies that have shown that the effectiveness of traffic calming measures has a strong positive correlation with the height dimension of the vertical speed control device [43][44][45]. Zone 3, on the other hand, provides an overall "acceptable" performance and can be considered sufficiently suitable for the role of traffic calming aimed at limiting the driving speed below the legal limit of 30 km/h.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, the analogous measure consisting of the sequence of speed tables in Zone 2 (h = 4 cm) results in a significant tendency of road users to drive at speeds above the 30 km/h limit, which is insufficient overall to fulfil the task of limiting speed within the prescribed limit. These results are in agreement with numerous previous studies that have shown that the effectiveness of traffic calming measures has a strong positive correlation with the height dimension of the vertical speed control device [43][44][45]. Zone 3, on the other hand, provides an overall "acceptable" performance and can be considered sufficiently suitable for the role of traffic calming aimed at limiting the driving speed below the legal limit of 30 km/h.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, the type of vehicles on residential roads can range from motorcycles to middle-sized lorries. The speed limit for residential roads is typically below 35 km/h but the actual travel speed of vehicles may range from 18.6 km/h to 44.7 km/h [6][7]. As for the parking lots inside of buildings, the vehicles are typically motorcycles and cars while larger vehicles such as lorries are designated for the loading bay and their assigned sections.…”
Section: Introductionmentioning
confidence: 99%
“…The rotational kinetic energy of the main shaft will supply the DC generator. The power transferred to the DC generator can be obtained from equation(7).18th International Engineering Research Conference 2022 (Eureca 2022) Journal of Physics: Conference Series…”
mentioning
confidence: 99%
“…Various types of road humps are either prefabricated or built on-site, and different designs are often used. Geometric and layout designs must be taken into consideration in order to effectively control the vehicle speed [4]- [8]. The geometric design of speed humps deals with the shape and size of individual road humps.…”
Section: Introductionmentioning
confidence: 99%